BERMAIN UNO MODIFIKASI TERHADAP KEMAMPUAN MENGENAL KONSEP BILANGAN PADA ANAK AUTIS - R, KHOFIDHOTUR (Jurnal Pendidikan Khusus, 2016)
ABSTRACT Autism children had disturbance in cognitive i.e. recognizing numbers concept. It happened because of less interesting learning, less motivating children, and monotone. Therefore, it required learning which was appropriate with the autism children characteristics. The obstruction in recognizing numbers concept would be overcome by playing Uno modification. Playing Uno modification was playing Uno activity which gave priority to equation number and the activities of counting, matching, putting in order, and writing number 1-9 in the rule game so it utilized for learning numbers concept recognition. Playing Uno modification was also fun, interesting, and modern playing activity and new game for the children. The purpose of this research was to prove the influence of playing Uno modification toward the ability of recognizing numbers concept to autism children. This research used quantitative approach with pre experiment kind and used the arrangement of one-group pre-test and post-test design with the subject 6 autism children. The sampling technique in this research used purposive sample i.e. taking the sample based on the characteristics which was the population main characteristics. The technique of data collection was test and documentation. The technique of data analysis used statistic non parametric Wilcoxon Match Pairs Test. The research result indicated that the ability of recognizing numbers concept before using playing Uno modification was 51,25 whereas the ability of recognizing numbers concept after using playing Uno modification was 77,5. It indicated that there was enhancement. In addition, the research result also indicated Z counted = 2,2 was greater than Z table = 1,96 with crisis value 5%. If Z counted = 2,2 > Z table = 1,96 so it could be concluded that there was influence of playing Uno modification toward the ability of recognizing numbers concept to autism children   Keywords: Numbers, Playing Uno Modification.